Spinel-containing alumina-based refractory castables - Braulio, M.A.L.; Rigaud, M.; Buhr, A.; Parr, C.; Pandolfelli, V.C. (Ceramics international, 2011)
Due to their high corrosion resistance to basic slags, either pre-formed or in situ spinel (MgAl 2O 4) containing refractory castables are nowadays widely used as steel ladle linings. Nevertheless, whereas the pre-formed spinel castables present high volumetric stability and a well-known processing technology, the in situ spinel castables still require further understanding due to the challenges related to magnesia hydration and their expansive behaviour at high temperatures. Therefore, the objective of this paper is to review the knowledge already available for high-alumina spinel-containing castables (preformed and in situ) in order to provide a support for novel technological developments in the area. The main variables considered are the spinel content and grain size, the effect of calcium aluminate cement and hydratable alumina on the general castables’ properties, the influence of different alumina and magnesia sources and the silica fume content. Nowadays research subjects, including the use of mineralising compounds, the addition of nano-scaled particles and the evaluation of the effect of expansion under constraint will also be addressed, pointing out alternatives for the design of high-performance alumina-magnesia refractory castables.